An interpretable deep learning approach to detect Alzheimer using MRI images - Oni, Farhan Anzum; Hossain Sayem, Kazi Sazzad; Rahman, Mushfiqur; Kabir, Sanjida; Bhuiyan, Fardeen Yousuf (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.